Distortion Inspection System Development of Rearview Mirror using Radial Line Method Based on Image Processing - Detak Yan Pratama; Apriani Kusumawardhani; Aulia M T Nasution; Andi Rahmadiansyah; Achmadi Achmadi (IPTEK Journal of Proceedings Series, 2015)
Quality control is one of the important steps in production process of rearview mirror industry. This activity can be in the form of product inspection. As an essential component of vehicle, rearview mirror must be observed especially in distortion assessment. During this time, the assessment of rearview mirror product is finished by experts. Thus, faults of inspection can be occurred. These faults could be caused by a decrease of accuracy which is an effect of eyes tiredness. The technique of image processing method is observed to solve this inspection problem. This study is proposed to construct the distortion inspection system on rearview mirror by using radial line method based on image processing.